Ética e educação ambiental: práticas docentes da educação básica de Nova Santa Rosa – Paraná - Diniz , Antonio Marcos (2020)
This study questions the presence of environmental ethics and environmental education in formal education, more specifically in basic education in the municipality of Nova Santa Rosa, western Paraná. The general objective was to investigate the teaching practices on Environmental Ethics and Environmental Education in Basic Education through the characterization of the teacher profile in the context of Environmental Education in Basic Education, recognition of how the knowledge on Environmental Ethics and Environmental Education is structured, in addition to the debate how Environmental Ethics is present in Sustainable Rural Development. The study consisted of a bibliographic review about Environmental Ethics and Environmental Education and outlines the daily and professional practices of 75 teachers of Basic Education in Nova Santa Rosa. The study concludes the precariousness of Environmental Ethics and Environmental Education in the initial and continued training of the vast majority of teachers, evidencing the presence of Education A in school documents. Likewise, it demonstrates an asynchrony between the care for the environment in the speeches and their professional practice in relation to Environmental Education. So we believe that if not all, the vast majority of study participants are clear that concerns about the environment, with the depletion of natural resources, with climate change, with climate disasters due to man's constant search for profit, without reflection about future generations, we finally identified a certain concern with the moment of crisis we are experiencing, environmental crisis, ethical crisis, although we also apprehend that, unfortunately there is only this concern, very little is being done to change these situations. We consider that the study does not end here, we have at most raised some questions that should be appreciated in a deeper study, so that with more time and interventions necessary to transform our utopias into reality.